Addressing Nitrogen Hunger in Agroecosystems: Balancing Food Security and Environmental Stewardship - Ajay Kumar Bhardwaj (Journal of the Indian Society of Soil Science, 2026)
I am deeply honored to deliver the 10th Dr. S.N. Saxena Lecture, organized by the Modipuram chapter of the Indian Society of Soil Science. I pay my heartfelt homage and tribute to Dr. S.N. Saxena, one of India’s pioneering soil scientists, whose visionary work established new schools of thought and made significant contributions to the field of soil science. His legacy continues to inspire and guide our work today.